Hive [games] : a game crawling with possibilities - Yianni, John (Smart Zone ; Gen42 Games, 2017)
The object of the game is to totally surround your opponent's Queen bee while at the same time trying to stop your opponent from doing the same to you. The pieces surrounding the Queen Bee can be made up of a mixture of both your pieces and your opponent's. The first player to surround their opponent's Queen Bee wins.